Low birth weight: Risk factors - Chávez, Wilber (2015)
Objective: To determine low newborn weight risk factors (LBW). Setting: Hospital Apoyo III, Ministry of Health, Sullana northern Peruvian urban City. Design: Transversal, retrospective, analytical, case-control study. Material and methods: One thousand five hundred and thirty-six LBW in 15318 newborns delivered between June 1994 and December 1999. Information was obtained from Perinatal Informatic System. Analysis used programs EPI INFO and SPSS 10,1. Results: LBW incidence was 10,02%. Preconceptional causes were nulliparity, maternal size below 1,50 m, age below 19 years; conceptional causes were maternal pathology, non- or inadequate prenatal control. Maternal pathologies were anemia, urinary tract infection, preeclampsia and premature rupture of membranes. Conclusions: Preconceptional risk factors were previous arterial hypertension, maternal weight and size, being illiterate and nulliparity; and conceptional risk factors, threatened premature delivery, second trimester hemorrhage, multiple pregnancy, third trimester hemorrhage, and eclampsia. Risk factors attributable to the population were maternal pathology, lack or inadequate prenatal control, threatened premature delivery, multiple pregnancy, and chronic anemia.